210Polonium bioaccessibility assessment in algae for human consumption: An in vitro gastrointestinal digestion method. Issue 4 (16th February 2017) - Desideri, Donatella; Meli, Maria Assunta; Roselli, Carla; Feduzi, Laura; Ugolini, Lucia
ABSTRACT: The occurrence and mobility of natural radioactive element as 210 Polonium ( 210 Po) in 13 commercial algae consumed in Italy by humans were determined because the effects on human health need to take into account the bioavailability of these elements. The simulation of gastrointestinal (GIT) digestion was divided into three stages and was accomplished using three different artificial solutions: saliva, gastric, and synthetic bile–pancreas solution. The same sample was treated in two different ways: a) only gastric digestion and b) complete GIT digestion (gastric digestion followed by bile–pancreas solution). The difference between Po gastric mobility with respect to that found for GIT digestion was not significant; in fact, Po mobility exhibited a mean value 17.2 ± 15.1% and 19.5 ± 11.5% for gastric and GIT digestion, respectively.